Genetic Divergence Analysis for Yield and Quality Traits in Garden Pea (Pisum sativum L.) - Bijalwan, Priyanka; Raturi, Akhilesh; Mishra, A. C. (International Journal of Bio-resource and Stress Management, 2018)
Genetic diversity among twenty-three pea genotypes was worked out using Mahalanobis D2 statistic. On the basis of genetic distance, these genotypes were grouped into 5 clusters. Cluster IV was largest, consisting of eight genotypes followed by cluster I with seven genotypes, cluster III with four genotypes, cluster II with three genotypes while cluster V contained single genotype. There was no parallelism between genetic diversity and geographical distribution. Cluster IV (PSM-3, Pea-901, CHP-2, AP-2, AP-5, VRP-6, PSM-4 and Pea 902) and cluster V (Pb-89) exhibited highest value of inter-cluster distance (377.64) followed by cluster III (PC-531, AP-1, VRP-7 and VL-7) and cluster V (284.18), cluster II (PSM-5, E-6 and Pant Uphar) and cluster V (214.09) and cluster I (PM-2, Pea-801, Arkel, Arka Ajeet, AP-3, JM-1 and AP-4) and cluster V (168.02). The maximum intra-cluster distance was noted for cluster IV (25.89). Cluster V exhibited maximum mean values for pod yield for plant, TSS, pod length, number of pods plant-1, fresh weight of root nodules plant-1, root length, number of flowers cluster-1 and days to 50% flowering. The character fresh weight of root nodules plant-1 contributed maximum towards divergence. Considering diversity pattern and other performance of the genotypes PSM-3, Pea-901, CHP-2, AP-2, AP-5, VRP-6, PSM-4 and Pea-902 from cluster II and genotype Pb-89 from cluster V may be taken into consideration as better parents for an efficient hybridization programme of pea.